Pemberian Pupuk Kompos Kotoran Burung Puyuh dan POC Limbah Kulit Nanas terhadap Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis Hypogaea L.) - Ilham Azhari; Iwan Hasrizart; Nuraida Nuraida (Jurnal Agrofolium, 2024)
Peanuts (Arachis hypogaea L.) in Indonesia are the most important agricultural commodity after soybeans which have a strategic role in national food as a source of protein and vegetable oil. Quail droppings are a type of hot fertilizer, decompose quickly so they are directly absorbed by plants because they contain macro nutrients (Ca, P, N, K, and CI) and micro nutrients (Fe, Cu, Zn, Mn, and Mo) required by plants (Kusuma, 2012). Pineapple peel waste can also be used as organic fertilizer in solid or liquid form, test results show that the POC of Pineapple Peel Waste is P (23.63 ppm), K (08.25 ppm), N (01.27 ppm), Ca (27.55 ppm ), Mg (137.25 ppm), Zn (0.53 ppm) and Organic C (3.10%). This research aims to determine the application of quail manure compost and pineapple peel waste to the growth and production of peanut plants (Arachis hypogaea L.). This research was carried out in Pematang Setrak Village, Teluk Mengkudu District, Serdang Bedagai Regency, North Sumatra Province, from June to August 2023, this research used a Factorial Randomized Block Design with 2 factors studied and 3 replications where the first factor was quail manure (P) which consisted of 4 levels, namely P0 (without treatment), P1 ( 1 kg per plot), P2 (2 kg per plot), P3 (3 kg per plot). The second factor is the POC of pineapple peel waste (N) which consists of 3 levels, namely N0 (without treatment), N1 (35 ml liter-1 of water), N2 (70 ml liter-1 of water). The parameters observed were plant height (cm), number of filled pods per sample plant (pods), pod weight per sample plant (g), pod weight per plot and seed weight per 100 sample seeds.The results of the research showed that the application of quail manure compost had a very significant effect on the parameters of the number of filled pods per sample plant, pod weight per sample plant, pod weight per plot and seed weight per 100 sample seeds, but had no significant effect on the plant height parameter. Providing POC from pineapple peel waste had a very significant effect on the parameters of the number of pods contained per sample plant, pod weight per sample plant, pod weight per plot and seed weight per 100 sample seeds. The interaction between giving quail manure compost and pineapple peel waste POC had a very significant effect on the parameters of number of filled pods per sample plant, pod weight per sample plant and pod weight per plot, but had an insignificant effect on the parameters of plant height and seed weight per 100 sample seeds. .